2022
DOI: 10.1039/d2en00144f
|View full text |Cite
|
Sign up to set email alerts
|

SO2-Tolerant catalytic reduction of NOx by confining active species in TiO2 nanotubes

Abstract: It is still a great challenge to selective catalytic reduction (SCR) of NOx in the presence of SO2. Herein, active Cu species confined in TiO2 nanotubes (TiO2 NTs) as SCR...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…For cerium sulfate (Figure 4c), the bands at 1367 and 1300 cm −1 are related to the asymmetric stretching frequencies of O=S=O species [32]. The band at 1660 cm −1 is assigned to O-H stretching modes from the reaction between SO2 and surface hydroxyl groups [33,34]. As for ammonium cerium sulfate, five characteristic bands are observed in Figure 4d.…”
Section: Surface Groups Identificationmentioning
confidence: 95%
See 1 more Smart Citation
“…For cerium sulfate (Figure 4c), the bands at 1367 and 1300 cm −1 are related to the asymmetric stretching frequencies of O=S=O species [32]. The band at 1660 cm −1 is assigned to O-H stretching modes from the reaction between SO2 and surface hydroxyl groups [33,34]. As for ammonium cerium sulfate, five characteristic bands are observed in Figure 4d.…”
Section: Surface Groups Identificationmentioning
confidence: 95%
“…The IR spectrum of the CeNbTi that was treated in a simple SCR condition is shown in Figure 4e as the background. The band at 1617 cm −1 is assigned to adsorb H2O from the reaction between SO2 and surface hydroxyl groups [33]. The band at 965 cm −1 is attributed to characteristic vibrations of Nb=O bond in surface NbOx species [23] and the one at 1128 cm −1 is due to modes of Nb-O-Nb stretching vibration [38,39].…”
Section: Surface Groups Identificationmentioning
confidence: 99%
“…It is noted that the peak at 1637 cm −1 belonging to H 2 O species discovered after 7 minutes, produced from the surface OH group bonded with SO 2 , and it gradually vanished after 11 minutes. 58 Previous literature suggested that more OH groups on the surface would alleviate the sulfation of active sites, protecting the Mn sites to successfully carry on NH 3 -SCR. 59 For Ho-TNTs/ Mn, as shown in Fig.…”
Section: Thermogravimetric Analysis Of An So 2 -Treated Catalystmentioning
confidence: 99%
“…SO 2 can react with active metal oxides via competitive adsorption to form inactive metal sulfates, resulting in blocking of the active sites. 19,20 To improve SO 2 -tolerance, one strategy is to regulate the surface electronic properties of catalysts; the other approach is to introduce an active phase as a scavenger to preferentially capture SO 2 . 21,22 Xu et al revealed that V doping into a 13Cu/γ-Al 2 O 3 catalyst exhibited acceptable SO 2 resistance of the 13Cu/γ-Al 2 O 3 catalyst for toluene oxidation owing to the synergy between Cu and V oxide.…”
Section: Introductionmentioning
confidence: 99%